2021
DOI: 10.15252/emmm.202114434
|View full text |Cite
|
Sign up to set email alerts
|

Correction of oxidative stress enhances enzyme replacement therapy in Pompe disease

Abstract: Pompe disease is a metabolic myopathy due to acid alpha‐glucosidase deficiency. In addition to glycogen storage, secondary dysregulation of cellular functions, such as autophagy and oxidative stress, contributes to the disease pathophysiology. We have tested whether oxidative stress impacts on enzyme replacement therapy with recombinant human alpha‐glucosidase (rhGAA), currently the standard of care for Pompe disease patients, and whether correction of oxidative stress may be beneficial for rhGAA therapy. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 101 publications
(150 reference statements)
3
4
0
Order By: Relevance
“…In line with this, Cardone et al found a marked surface CI-MPR reduction that correlated with PD severity [ 42 ], pointing to defects in receptor recycling as the driver of this phenomenon. This reduction in surface CI-MPRs in Pompe patients’ cells was confirmed by several authors [ 52 , 56 ]. All of our murine cellular models presented lower surface expression of CI-MPRs, although this reduction was highly variable depending on culture conditions (data not shown).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In line with this, Cardone et al found a marked surface CI-MPR reduction that correlated with PD severity [ 42 ], pointing to defects in receptor recycling as the driver of this phenomenon. This reduction in surface CI-MPRs in Pompe patients’ cells was confirmed by several authors [ 52 , 56 ]. All of our murine cellular models presented lower surface expression of CI-MPRs, although this reduction was highly variable depending on culture conditions (data not shown).…”
Section: Discussionsupporting
confidence: 81%
“…Being aware of the genetic and physiological interspecific differences between the gold-standard GAA-KO model and most PD patients, we first generated murine muscle cell models using genome editing to reproduce relevant PD mutations listed in the PD database [ 50 , 51 ]. Interestingly, in addition to succeeding in abrogating GAA activity, all cellular models generated for this work presented several phenotypic defects characteristic of PD, such as increased autophagic build-up and glycogen accumulation as well as a downregulation of surface CI-MPRs, a phenomenon that has been reported previously only in fibroblasts from Pompe patients [ 42 , 52 ].…”
Section: Discussionmentioning
confidence: 61%
“…Quantitative measurements (Supporting Information) confirmed visual observations -NAD(P)H levels were significantly reduced in the buildup areas (Figure 1D), in agreement with the disruption of mitochondrial morphology/function previously reported by us and others. 8,9 Next, we explored the possibility of evaluating therapeutic efficacy by using non-invasive imaging of the tongue muscle as a substitute for skeletal muscle (tongue involvement in Pompe patients is described in Supporting Information). This would allow for extended follow-up to monitor the disease progression and the effect of therapies.…”
Section: E T T E R T O T H E J O U R N a L Intravital Imaging Of Musc...mentioning
confidence: 99%
“…Quantitative measurements (Supporting Information) confirmed visual observations – NAD(P)H levels were significantly reduced in the buildup areas (Figure 1D ), in agreement with the disruption of mitochondrial morphology/function previously reported by us and others. 8 , 9 …”
mentioning
confidence: 99%
“…As oxidative stress is linked to dysfunctional autophagy in PD pathogenesis, a pre-clinical study recently evaluated the association between ERT and antioxidant agents, suggesting that they may improve GAA activity in rhGAA-treated cells [ 212 ]. The use of splice-switching antisense oligonucleotides (AOs) has also been investigated.…”
Section: Treatment Approachesmentioning
confidence: 99%